Clinical Profile of Cases of COVID-19 in Far Western Province of Nepal - Joshi, Jagadish; Mishra, Pradip; Kamar, Sher Bahadur; Sharma, Nirajan Datta; Parajuli, Janaki; Sharma, Seema; Pandey, Hem Raj (Journal of Nepal Health Research Council, 2020)
The novel coronavirus (COVID-19) cause various symptoms such as pneumonia, fever, breathing difficult and lung infection. Till now, total 9 cases are reported in Nepal and 4 cases from this province. This case series is to describe the initial clinical features of COVID-19 among the patients admitted in isolation ward of Seti Provincial Hospital. Oropharyngeal swab was taken from all four patients and sample was transfer to national reference laboratory. Three patients were coming from infected country and one is local transmission. Age of patients was range from 20 to 40 years of age with male preponderance. The patient coming from United Arab Emirate was presented with mild symptoms and others were asymptomatic. More tests, contact tracing and keeping them in quarantine are the necessitated action need to be taken by government of Nepal. Keywords: COVID-19; local transmission; oropharyngeal swab